(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
South African schools are governed by the South African Constitution of 1996 which prescribes the promotion of democratic values. This prescription cascades down to inform the Curriculum and Policy Statement (CAPS) that provides a curriculum policy framework for implementation. Schools are not only centring of learning that provide the rudiments and foundations of future learning, but indispensable centres for socialisation and transmission of social norms, values, and appropriate social behaviours. South African teachers have the mammoth task of being both the transmitters, role models, and teachers of democratic values as enshrined in the South African Constitution. The main question this study seeks to answer is: how can primary school history lessons be utilised to inculcate democratic values? Teaching democratic values through history lessons in primary schools remains a paradox, in the sense that, as a teacher you have to teach what is in the textbook, without being bias even though as a teacher you might you might have a different opinion on. Moreover, the inconsistencies in the era of fake news, conspiracy theories within the South African context, as well as challenges of racial polarisation, economic deprivation, unemployment, and heightened social inequality have exacerbated the inconsistencies in history teaching. Thus, teaching democratic values in South African primary schools has become more important than ever before to mitigate the plethora of these challenges. The present study engages the Qualitative Content Analysis method to analyse qualitative data from documented information in texts, media, and academic articles. It is underpinned by the Ubuntu African Philosophy and it concludes that there is an alignment between the democratic values and the CAPS Policy document. Findings also point to the critical role of history teachers to inculcate democratic values, and use appropriate knowledge that must be based on facts and evidence.